2018
DOI: 10.7287/peerj.preprints.27113v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating local social-ecological knowledge to prioritise invasive species management

Abstract: There is a lot of uncertainty about how we pick the best invasive species management strategies to improve the environment, local economy, and human well-being, as invasive species management involves complex and multidimensional challenges. Invasive species management on inhabited islands is especially challenging, often due to perceived socio-political risks and unexpected technical difficulties. Failing to incorporate local knowledge and local perspectives in the early stages of planning can compromise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Local communities are most directly exposed to IAS, where they incorporate IAS into their livelihoods. Therefore, elucidating these links would provide important insight for understanding IAS's roles in socio-ecological systems since people perceive the effects of IAS according to the space, time, and social groups/status (i.e., gender, wealth status, and residency period) to which they belong [19][20][21][22]. Moreover, households and communities vary in their dependency on and usage of invasive species [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local communities are most directly exposed to IAS, where they incorporate IAS into their livelihoods. Therefore, elucidating these links would provide important insight for understanding IAS's roles in socio-ecological systems since people perceive the effects of IAS according to the space, time, and social groups/status (i.e., gender, wealth status, and residency period) to which they belong [19][20][21][22]. Moreover, households and communities vary in their dependency on and usage of invasive species [23].…”
Section: Introductionmentioning
confidence: 99%
“…P. juliflora invasions forced local residents to incur a range of costs or ecosystem disservices that lead to reduced human welfare and household wellbeing through the loss of household assets and livelihood outcomes [4]. Other households benefit from ecosystem services derived from IAS [4,21,24]. For instance, some studies identified some IAS as important sources of food, medicine, firewood, and aesthetic value [25,26].…”
Section: Introductionmentioning
confidence: 99%